Ganglion cyst arising from the composite occipito-atlanto-axial joint cavity in a cat - Aikawa, T.; Sadahiro, S.; Nishimura, M.; Miyazaki, Y.; Shibata, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2014)
A four-year-old, female spayed Domestic Longhaired cat was referred for evaluation with a two month history of initial inability to jump progressing to ambulatory tetraparesis. Magnetic resonance imaging studies demonstrated a cystic lesion arising from the composite occipito-atlanto-axial joint cavity and extending to the region of the occipital bone and the axis. The lesion surrounded the spinal canal, causing moderate dorsal spinal cord compression at the atlanto-occipital joint. A dynamic myelographic study demonstrated attenuation of the dorsal contrast column at the atlanto-occipital joint when the cervical spine was positioned in extension. Partial excision of the cyst capsule by a ventral approach resulted in long-term (64 months) resolution of clinical signs. Histological evaluation was consistent with a ganglion cyst. An intra-spinal ganglion cyst arising from the composite occipito-atlanto-axial joint cavity may be considered as an uncommon differential diagnosis for cats with cervical myelopathy.
Keywords: Ganglion cyst; synovial cyst; composite occipito-atlanto-axial joint; spine; cat